Saberes culturais e modos de vida de ribeirinhos e sua relação com o currículo escolar: um estudo no Município de Breves/PA - LIMA, Natamias Lopes de (Universidade Federal do Pará, 2012)
This study shows how the thematic curriculum and cultural knowledge, investigating the way the school curriculum of the riverside town of Breves relates to the cultural environment in which knowledge is integrated. From a broader perspective, the study aims to contribute to critical reflective thinking about curriculum in schools multigrade assumed the Amazon river. More specifically, the research aims to identify significant aspects of the cultural universe of the coastal municipality of Breves, investigating the knowledge present in the discourse and everyday practices of coastal community of Santa Maria and examine the curriculum in action, the relationship between school knowledge riparian and cultural knowledge, where the school is located. It is a field research conducted in a qualitative approach riverside community in the municipality of Breves, Pará State, anchored in different sources and substantiated by the research literature, the theoretical basis, from dissertations, theses, books, articles and other printed materials that deal with different theoretical matter, either from a more general context as Darcy Ribeiro (2006), regional and Samuel Benchimol (1999) and place as Cross (2008), Pacheco (2009) and others. The results indicate that although particular characteristics, both the coastal and culture are not something pure, isolated, unchanging or only produce them and what their ancestors way of life, cultural events in general, by contrast, are in a constant process change. The issues explored in the classroom have served more as a subterfuge to teach alphabet letters and nonsense syllables than as a reference point for a dialogue with the students. However, the curriculum developed at the Santa Maria school establishes a closer relationship with the cultural knowledge of the community bordering Santa Maria, as the issues that are closer to the cultural context of the students, were not found in textbooks used in school nor in the syllabus offered by the Education Department. In fact, these contents have been proposed by the teacher from the reality of the students